2009
DOI: 10.11606/issn.1981-0490.v12i2p173-187
|View full text |Cite
|
Sign up to set email alerts
|

Da excelência ao lixo: humilhação, assédio moral e sofrimento de trabalhadores em fábricas de calçados no Ceará

Abstract: Este artigo tem como objetivo discutir a vivência de humilhação e de sofrimento de trabalhadores da indústria calçadista com histórias de acidentes ou de adoecimento do trabalho, e também de competência e dedicação à empresa. É parte dos resultados da pesquisa "Violência e trabalho: acidentes de trabalho e humilhação na indústria calçadista do Ceará". A discussão fundamenta-se nos relatos de três trabalhadores de duas fábricas de calçados de grande porte instaladas no Ceará, selecionados entre 20 entrevistados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…This paper suggests that stress coping strategies are developed by the footwear industries focused on workers' emotions and work problem solving (Folkman & Moskowitz, 2004), as these variables contribute to the relief of emotional distress, accepting responsibility, self-control, escape strategies and identification of specifics stressful (Folkman & Lazarus, 1988;Dardas & Ahmad, 2015). As for 'job dissatisfaction' changes in the organizational climate of footwear industries may reflect on important improvements in this factor (Rueda et al, 2012), since studies in this industrial sector have demonstrated the suffering experienced by workers (Borsoi et al, 2009;Rigotto et al, 2010;Silva et al, 2017). However, to initiate changes in companies, it would be necessary to have laws covering psychosocial risks, such as the Framework Directive 89/391/EEC; this declares that employers are obliged to ensure workers' health and to guarantee a safe and healthy work environment, both in terms of physical and psychosocial conditions at work (European Commission, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper suggests that stress coping strategies are developed by the footwear industries focused on workers' emotions and work problem solving (Folkman & Moskowitz, 2004), as these variables contribute to the relief of emotional distress, accepting responsibility, self-control, escape strategies and identification of specifics stressful (Folkman & Lazarus, 1988;Dardas & Ahmad, 2015). As for 'job dissatisfaction' changes in the organizational climate of footwear industries may reflect on important improvements in this factor (Rueda et al, 2012), since studies in this industrial sector have demonstrated the suffering experienced by workers (Borsoi et al, 2009;Rigotto et al, 2010;Silva et al, 2017). However, to initiate changes in companies, it would be necessary to have laws covering psychosocial risks, such as the Framework Directive 89/391/EEC; this declares that employers are obliged to ensure workers' health and to guarantee a safe and healthy work environment, both in terms of physical and psychosocial conditions at work (European Commission, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The literature contains several studies indicating that WRMDs affect almost every body part of workers in this industry, including the arm (Amano et al, 1988), the neck (Serratos-Perez & Mendiola-Anda, 1993), the shoulder (Descatha et al, 2004;Leclerc et al, 2004), the hand/finger (Gupta & Mahalanabis, 2006), the elbow (Descatha et al, 2007), the upper back (Aghili et al, 2012), the lower back (Warnakulasuriya et al, 2012), the knee (Dianat & Salimi, 2014), the hip/thigh and ankle/foot (Silva et al, 2016). In addition, the Brazilian footwear industry is marked by a history of physical and psychological violence perpetrated by supervisors against shop floor workers (Borsoi et al, 2009;Rigotto et al, 2010). Previous studies in footwear industries have evaluated the influence of few psychosocial factors in WRMDs or did not consider their impact on the various parts of the body.…”
mentioning
confidence: 99%
“…Os trabalhos qualitativos, em sua maioria, pautam-se na ótica das vítimas, apresentando contextos diversos, como o bancário, o acadêmico, o fabril, além do setor público (BAILLIEN et al, 2009;BORSOI;RIGOTTO;MACIEL, 2009;CORRÊA;CARRIERI, 2007;LEWIS, 2006;MACIEL et al, 2007; PAIXÃO et al, 2014; SANCHES; MOTA; COSTA, 2011; TRACY; LUTGEN-SANDVIK; ALBERTS, 2006). Atenção às percepções de gestores de grandes empresas foi expressa na pesquisa de Teixeira, Munck e Reis (2011), e óticas múltiplas (processos jurídicos, vítimas, gerentes e agressor) foram evidenciadas no estudo Valadão Júnior e Mendonça (2015).…”
Section: Epistemologias E Abordagens Das Pesquisasunclassified
“…There are, in humiliation and aggression, reasons for abandonment of employment, much less have a clear vision of who suffer bullying, as this, for him, is unknown. 13 Therefore, bullying is occurring intentionally, without limitation, for the purpose of belittling the victim of a disciplinary way, leaving her confused and psychically without actions. The aggressor is seen by the organization as a contributor of profit and productivity, so that their attitudes of arrogance and domination go unnoticed, creating and making this scenario a location hidden.…”
Section: Contributions Of Psychologymentioning
confidence: 99%